Self-Concept of Refugee Children Living with Foster Parents in Indonesia: A Case Study of Refugee Children Cared for by Foster Parents - Uga Pratama Gunawan (Sean Institute, 2025)
This study aims to determine the self-concept of refugee children after receiving care from foster parents who are local Indonesian people. This study uses a qualitative method with a case study approach to find out how the self-concept is built by refugee children. The study was conducted in addition to using in-depth interviews with informants, both refugee children, foster parents, and the surrounding community. The data collection process in this study used interviews, in-depth observations, and documentation studies. Data analysis techniques used data reduction and triangulation. The results of the study of three refugee children who were cared for by foster parents from different cultural backgrounds generally showed positive results, and a relationship was found between the impact on care from a family to help children grow and develop properly as has been believed by child development experts. The care provided, in addition to helping children grow and develop, also has an impact on their adjustment to the local community and helps them develop a positive self-concept as found in the field. This positive self-concept is valuable capital for them in living their lives in the future.